2018
DOI: 10.1001/jamaneurol.2018.0894
|View full text |Cite
|
Sign up to set email alerts
|

Use of Flutemetamol F 18–Labeled Positron Emission Tomography and Other Biomarkers to Assess Risk of Clinical Progression in Patients With Amnestic Mild Cognitive Impairment

Abstract: IMPORTANCE Patients with amnestic mild cognitive impairment (aMCI) may progress to clinical Alzheimer disease (AD), remain stable, or revert to normal. Earlier progression to AD among patients who were β-amyloid positive vs those who were β-amyloid negative has been previously observed. Current research now accepts that a combination of biomarkers could provide greater refinement in the assessment of risk for clinical progression. OBJECTIVE To evaluate the ability of flutemetamol F 18 and other biomarkers to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 65 publications
4
59
0
1
Order By: Relevance
“… More comprehensive study details can be found in Wolk et al [ 11 ] CAC Clinical Adjudication Committee a Of those reviewed by the CAC …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… More comprehensive study details can be found in Wolk et al [ 11 ] CAC Clinical Adjudication Committee a Of those reviewed by the CAC …”
Section: Methodsmentioning
confidence: 99%
“…The aMCI patients were, on average, 10 years younger than the EoL patients (mean age 71 years, range 53–91 years) and comprised 232 patients who took part in a 3-year follow-up study to determine whether a positive [ 18 F]flutemetamol PET scan or positivity using other biomarkers would increase the risk of progression to AD (Table 2 ). The demographics and inclusion criteria for this study have been described by Wolk et al [ 11 ]. Of the 232 aMCI patients, 224 were reviewed by a Clinical Adjudication Committee (CAC) to assess conversion status [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…detecting amyloid pathology later confirmed at post-mortem (Ikonomovic et al, 2016;Sabri et al, 2015;Thal et al, 2015), comparable diagnostic utility to [ 11 C]PiB (Lowe et al, 2017;Villemagne et al, 2012), effectiveness in the prediction of conversion from MCI to AD (Ong et al, 2015;Wolk et al, 2018), and the clinical benefit of increased dementia diagnostic confidence (Schipke et al, 2012;Zwan et al, 2017). Associations are shown between Aβ uptake and cognitive dysfunction in AD (Barthel et al, 2011) and MCI (Bahar-Fuchs et al, 2013) for [ 18 F]florbetaben.…”
Section: F-labelled Amyloid Tracersmentioning
confidence: 98%
“…When considering the clinical implementation of this modality, recent evidence demonstrates its cost-effectiveness(Hornberger, Bae, Watson, Johnston, & Happich, 2017) and meaningful impact on the diagnostic confidence for AD by physicians(Boccardi et al, 2016).While not as widely investigated as [ 18 F]florbetapir, a similar pattern of amyloid retention is demonstrated throughout the cortex in AD using both [ 18 F]florbetaben(Barthel et al, 2011) and [ 18 F] flutemetamol(Nelissen et al, 2009). Additional commonalities shared by these two tracers with [ 18 F]florbetapir include high rates of sensitivity and specificity in diagnosing AD(Barthel et al, 2011;Hatashita et al, 2014;Rowe et al, 2008;Tiepolt et al, 2013;Vandenberghe et al, 2010;Villemagne et al, 2011) and detecting amyloid pathology later confirmed at post-mortem(Ikonomovic et al, 2016;Sabri et al, 2015;Thal et al, 2015), comparable diagnostic utility to [ 11 C]PiB(Lowe et al, 2017;Villemagne et al, 2012), effectiveness in the prediction of conversion from MCI to AD(Ong et al, 2015;Wolk et al, 2018), and the clinical benefit of increased dementia diagnostic confidence(Schipke et al, 2012;Zwan et al, 2017). Additional commonalities shared by these two tracers with [ 18 F]florbetapir include high rates of sensitivity and specificity in diagnosing AD(Barthel et al, 2011;Hatashita et al, 2014;Rowe et al, 2008;Tiepolt et al, 2013;Vandenberghe et al, 2010;Villemagne et al, 2011) and detecting amyloid pathology later confirmed at post-mortem(Ikonomovic et al, 2016;Sabri et al, 2015;Thal et al, 2015), comparable diagnostic utility to [ 11 C]PiB(Lowe et al, 2017;Villemagne et al, 2012), effectiveness in the prediction of conversion from MCI to AD(Ong...…”
mentioning
confidence: 99%